The effect of pressure on high- and low-working-memory students: An elaboration of the choking under pressure hypothesis - Wang, Zuowei; Shah, Priti (British journal of educational psychology, 2014)
Sample Fifty‐three third and fourth graders from China participated in this study. Method Participants' working memory (WM) was assessed by the Automated Operation Span task. Then, they solved mental addition problems of different types under low‐ and high‐pressure conditions. Performance was analysed as a function of pressure condition, working memory capacity, and problem type. Results On ‘no carry’ mental addition problems, there was no difference between the two groups of children regardless the presence of pressure. For problems with carries, low WM (LWM) children performed worse on all tasks compared with high WM (HWM) children in the no‐pressure condition, but pressure influenced the LWM and HWM differently depending on the nature of the carrying task. On ‘hidden carry’ mental addition trials (for which guessing strategies were minimally effective), LWM performance was much lower than HWM performance under pressure. By contrast, performance was similar between LWM and HWM groups under pressure on the ‘normal carry’ trials that allowed for non‐resource‐intensive heuristic strategies. Conclusion Whether high‐ or low‐working‐memory elementary‐school‐aged children were more or less affected by pressure was dependent on task‐difficulty and the types of strategies that could be used to solve the problems.